The Identification of Student Misconceptions on the Concept of Electricity Using the CRI Decision Matrix Three Level Test - Muhammad Azzarkasyi; Syamsul Rizal; Kasmawati Kasmawati (Universitas Syiah Kuala, 2019)
The purpose of this study is to determine the percentage of students who experience misconceptions (MIS), know the concept (KCC), do not know the concept (LK), Guess (LG), and not confidence (NC) in learning electricity concepts; in what subconcepts students experience misconceptions and what causes misconceptions. The object of the research was the first-level D-III students of Radiology Engineering in the first semester of the 2016/2017 school year who contracted the Basic Physics course. The study was conducted in November 2016. The method used is descriptive method. In this study the CRI Three-Tier Test decision matrix is used to identify student misconceptions. Identification is done by using a structured choice diagnostic test that is equipped with an index of student confidence in the test answers and also equipped with a column of reasons from the answers given by students. To find out the cause of the misconception conducted interviews. The results of CRI diagnostic data analysis showed that of the 37 students who were the object of research it was found that as many as 26.35% did not know the concept (LK), 20.95% knew the concept (KCC) where the students were in accordance with scientific conceptions, 0.51% students guessed LG), 40.88% of students experienced misconceptions (Mis), and 11.32% of answers to students who were not confident (NC). The highest percentage of misconception was found in the sub-principle of ohm's legal concept (41.08%), kirchhoff's legal sub-concept (41.89%) and sub-basic concepts of electric and parallel circuits (40.54%). The results of the interviews showed that the causes of the misconceptions included the character of abstract electrical concepts, lack of understanding of the concept, difficulty analyzing the sequence, and the unpreparedness of students to accept material delivered by the lecturer.